Retinoblastoma Situation in Burkina Faso over Ten Years: A Cross-Sectional Study - Ouattara, Amadou; Beremwidougou, Anicet Corneille; Sankara, Paté; Traore/Dolo, Mariam; Meda, Tierinyê Armand; Djiguimde, Windinmanégdé Pierre; Kabore, Rolande; Bouda, Chantal Gabrielle; Meda/Hien, Gertrude Augustine; Sanou, Jerome; Diallo, Jean Wenceslas; Zabsonre/Ahnoux, Ahgbatouhabeba (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Background: Retinoblastoma is the most common malignant intraocular tumor in children. The incidence of retinoblastoma appears to be higher in developing countries. In Burkina Faso, there is only one retinoblastoma treatment center located in the capital. Nowadays, the treatment of retinoblastoma has benefited from the contribution of scientific progress. Objective: The aim was to take stock of the situation of retinoblastoma in the pediatric oncology department from January 1, 2010 to December 31, 2019. To assess the situation over a 10-year period, the epidemiological, diagnostic, therapeutic, and evolutionary characteristics of children with retinoblastoma were studied. Materials and Methods: This was a descriptive cross-sectional study with retrospective data collection over a 10-year period, based on records of patients admitted to pediatric oncology department of CHU-YO. The study population consisted of all patients aged 0 - 14 years with retinoblastoma admitted to the pediatric oncology department. Data were analysed using CS Pro version 7.2 software. Categorical variables were compared using Pearson’s Chi-square test at the 5% significance level. Overall survival was estimated using the Kaplan-Meier method. Operational definitions were used for loss to follow-up, consultation and diagnosis delays. Results: A total of 204 cases were collected in 10 years, i.e. an annual average of 20.4 cases/year. The mean age at diagnosis was 37.5 months for unilateral cases and 26.4 months for bilateral cases. Male predominance was noted, with a sex ratio of 1.31. The majority of patients came from disadvantaged backgrounds (72% farming fathers and 91% housewives). Clinically, leukocoria and exophthalmos were the main presenting features. The average time to consultation was long (8.73 months) and unilateral localization was predominantly unilateral at 77%. In terms of treatment, 102 patients were eligible for curative treatment and 80 for palliative treatment. The prognosis was poor, with 41% death and numerous cases of loss to follow-up (18%). Overall survival was estimated at 32%. The factor associated with the lethality of retinoblastoma was the extension of the tumor to other organs. Conclusion: Recognition of the early clinical signs of retinoblastoma can anticipate the occurrence of this cancer. Health professionals should be encouraged to perform the Buckner test every time they come into contact with children aged 0 to 5, and the public should be encouraged to examine their children’s eyes. The study also recommended that parents need to be informed more about the need for regular and permanent monitoring for conclusive results of care.